Uprawnienie duchownych do przepowiadania Słowa Bożego w świetle Kodeksu Prawa Kanonicznego z 1983 r. - Domaszk, Arkadiusz (Prawo Kanoniczne, 2007)
Ministers help people to recognize Christ’s face. One of the many ways to do it is preaching the Word of God. This article analyzes preaching functions of ministers in the actual canon law. Bishops are responsible for the ministry of the divine word. They can preach on the whole world. In a particular church they are moderators of the preaching. Presbyters and deacons help in this function. In the actual canon law they can preach because their ordinations. This is a change with the previous law. Faculty of the preaching could be restricted by a com petent ordinary or particular law, and it is used with a presum ed consent of the rector of the church. Some theological and canonical problems in preaching are with the expression „in persona Christi”. Ministers preach „in persona Christi”, especially during the Holy Mass. This fact eliminates lay preaching in the Eucharistic, but it needs some more searching.